Perencanaan Desain Instalasi Pengolahan Air Limbah dengan Metode Biofilter Anaerob – Aerob - Neshart, Neshart; Rosdiana, Rosdiana; Wibowo, Dwiprayogo; Sukri, Ahmad Syarif (Jurnal TELUK: Teknik Lingkungan UM Kendari, 2021)
Planning design of wastewater treatment plant in a market is needed to improve the quality of water that will be discharged so it doesn’t pollute the environment and the near. The goal of this study is to determine the discharge of wastewater will be treated and the design of treatment basin in the wet lods area of Mandonga Traditional Market. Result of wastewater is 7.88 m3/day with a waste concentration of pH 7, BOD 64.2 mg/day, and TSS 2.130 mg/day. Wet Lods Wastewater Treatment Plant in Mandonga Traditional Market has 6 compartments such as a control tub with the fine filter addition which has a volume of 0.072 m3/day, the initial settling tank has a volume of 1 m3/day, anaerobic biofilter has a volume of 1.83 m3/day, aerobic tubs have a volume of 0.42 m3/day, the final settling tank I has a volume of 1.1 m3/day and the final settling tub II has a volume of 1.1 m3/day.